Transformation of Institutions from Line-Item Budgeting to Program Budgeting in the Context of Expenditure Rationalization, Implementation of Planned Objectives: Prospects and Challenges - Brahim, Lekmouta; Slimane, Atir; Laid, Amamra Med; hamza, Tidjania; hichem, Lebza; elhadi, Dhifallah mohammed (Journal of Ecohumanism, 2025)
This research aims to examine the issue of rationalizing public expenditures in light of the recent transformations in budget preparation and execution methods, with a focus on the transition from the traditional operating budget to the program-based budget as a modern approach grounded in results and performance. The study addresses the role played by the program-based budget in improving the efficiency of resource allocation, enhancing transparency, and linking public spending to predefined objectives, while highlighting the prospects offered by this shift and the organizational, financial, and human challenges that hinder its implementation. The research adopts a descriptive-analytical methodology through the analysis of relevant literature and studies, leading to a set of findings and recommendations that can support the effectiveness of budgetary reforms and achieve sustainable development.